Diseño de las instalaciones eléctricas e implementación de la puesta a tierra de protección de la "Unidad Educativa Mariano Negrete". Para reducir las fallas del sistema. - Chicaiza Rodríguez, Ayrton Raúl (2020)
This research has developed electrical system design of Mariano Negrete High School, to reduce electrical faults at the campus. As first step the information was collected, through this deterioration and failures were evidenced in electrical installations. It proceeds to perform lifting of loads to recognize how electrical circuits are distributed in the building, subdivided into three blocks. The High School has no plans for the electrical installations. To determine the number of luminaires required for each environment type, the DIALUX program was used. Force system was based on NEC regulations, chapter 15 Article 15.1.11.3, which indicates the number and type of currents that must be implemented in educational establishments. Concerning the tables of loads they will have several circuits, the type of protection, the caliber of the driver, and the areas that supply electrical energy, for all of them NEC regulation has been applied. To estimate the demand and the design of ground outlet Quito Electricity Company rules were used, that determined the capacity and the type of transformer, and resistance level. Therefore, applying NEC at electrical installations design at Educational Unit, Mariano Negrete will provide safe and reliable, the result of ground resistance was 3.32 ohms.